β-Nicotinamide adenine dinucleotide (β-NAD) acts as a bronchodilator - Innokentij Jurastow; Silke Wiegand; Amir Rafiq; Anna Zakrzewicz; Sandra Engel; Adriano Sanna; Daniel von der Beck; Walter Klepetko; Andreas Hecker; Andreas Günther; Moritz Bünemann; Gabriela Krasteva-Christ; et al. (PLoS ONE, 2025)
Introduction β-Nicotinamide adenine dinucleotide (β-NAD) is recognized as a sympathetic neurotransmitter that relaxes vascular and intestinal smooth muscle through purinergic receptor pathways. In the lung, β-NAD has been associated with anti-inflammatory effects, but its role in regulating airway smooth muscle tone remains unexplored. This study investigates the impact of β-NAD on airway smooth muscle and elucidates the underlying mechanisms of its action. Materials and methods Airway constriction was assessed as a force in organ bath (mouse trachea, human bronchioli) and as a luminal area in mouse precision-cut lung slices. The latter was combined with recording changes in [Ca2+] and membrane potential. Intracellular calcium and cyclic AMP concentrations were recorded in isolated airway smooth muscle cells. Results β-NAD did not affect baseline tension/area in the trachea, bronchi, and bronchioli. Airways precontracted with muscarine were concentration-dependently relaxed with β-NAD by up to 100%, being as effective as salbutamol. The airway relaxing effect of β-NAD was resistant to purinergic inhibitors, to inhibition of Gs- and Gi-signaling, and insensitive to several other blockers of common relaxation pathways. Isolated airway smooth muscle cells and bronchial smooth muscle in precision-cut lung slices responded to β-NAD with increased [Ca2+]i and depolarization of the cell membrane while relaxing. β-NAD increased intracellular cAMP levels in airway smooth muscle. In silico analysis revealed low expression of soluble adenylyl cyclase (ADCY10) in mouse and human airway smooth muscle, consistent with the lack of effect of the sAC inhibitor KH7 and preserved responses in sAC-deficient mice. These findings implicate transmembrane adenylyl cyclases as the likely cAMP source. Phosphodiesterase-4 inhibition with rolipram enhanced β-NAD-induced relaxation, suggesting a role for compartmentalized cAMP signaling. Conclusions Extracellular β-NAD relaxes airway smooth muscle via a noncanonical, cAMP-linked pathway that is independent of classical Gi- and Gs-coupled receptor signaling. This pathway is enhanced by PDE4 inhibition and likely involves localized cAMP pools generated by transmembrane adenylyl cyclases. These findings identify β-NAD as a potential modulator of airway tone and support further exploration of its physiological and therapeutic relevance.